Development of ARCS-based biology e-module to enhance students’ learning motivation and scientific argumentation skills - Yulia Lestari; Heffi Alberida; H. Helendra; Azwir Anhar (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
This in biology courses at the high school level, complex material often requires in-depth understanding and the ability to present arguments logically. This study aims to produce teaching materials in the form of ARCS-based biology e-module that are valid, practical, and effective for Phase E students in odd semesters in biology subjects, especially in ecosystem material. This development research is based on the unavailability of innovative teaching materials that can improve students' motivation and argumentation skills at Islamic Senior High School (MAN) 1 of Padang Panjang. The development procedure uses the ADDIE model which consists of five stages, i.e. analysis, design, development, implementation, and evaluation. The instruments used were validity questionnaires, practicality questionnaires, motivation questionnaires and test sheets. The data analysis technique used the t-test to testing the research hypothesis. The results of the study show that the teaching materials developed have met the aspects of validity, practicality, and effectiveness. The results of the validity test show that the ARCS-based biology e-module has very valid criteria. The e-module has also met the practicality aspect as seen from the teacher's response with the very practical criteria, and by students with the very practical criteria. The results of the t-test show that there is a significant difference between the average value of students' motivation and argumentation skills before and after using the product. Based on this, the ARCS-based biology e-module that has been developed is considered effective in improving the motivation and argumentation skills of class X students.